Experimental Investigation on Water-Exit Dynamics of Slender Cylinders: Effects of Velocity, Geometry, and Material Properties - Hualin Zheng; Hongfu Qiang; Yujie Zhu; Dudou Wang; Yuxiang Liu; Xiafei Guan (Journal of Marine Science and Engineering)
This work studies the water-exit problems of slender cylinders under various conditions through experimental investigation. An experimental platform was equipped with high-speed photography. A total of 13 experimental cases with varying head shapes (conical, spherical, and truncated cone designs), length-to-diameter ratios (5:1–7:1), ejection velocities (7.24–17.93 m/s), and elastic moduli (227.36–279.14 MPa) were conducted to capture water-exit characteristics. The investigation identified ejection velocity as the predominant parameter governing cavity morphology and stability, with higher velocities correlating to increased cavity dimensions and reduced drag coefficients by 54%. Conical head shape resulted in superior drag reduction characteristics, forming a typical cigar-shaped cavity with clear and regular boundaries. Additionally, an increased length-to-diameter ratio substantially improved drag reduction performance by 33%. Material elastic moduli proved crucial for water-exit stability, as cylinders with lower moduli experienced severe bending deformation and even trajectory changes, while higher moduli cylinders maintained their form with minimal deformation. This study illuminates the physical mechanisms of slender body water-exit under multi-factor coupling conditions, providing experimental evidence and theoretical guidance for cross-media vehicle design and underwater equipment optimization.